Study on the effects of polycrystal grain orientations on indentation hardness. (1st January 2012) - Zheng, Wei; Wang, Guangchun; Lin, Xiaojuan; Jiang, Hua; Wei, Dongbin; Jiang, Zhengyi
The effects of polycrystal grain orientations on the indentation hardness were studied by both the experimental investigation and numerical simulation. The surface grain orientations of the sample were measured using the electron back scatter diffraction (EBSD) technique, and are divided into three types of grains according to the characteristics of orientations. The indentation experiment was carried out on the surface grains with various orientations as the same direction of the indenter axis. According to the polycrystalline plastic forming theory, a new finite element method (FEM) model was established and the indentation processes on the grains with orientations of [111] and [100] were numerically simulated. By comparing the hardness from simulation results with those of experiments, the new FEM model considering grain orientations was validated. The forming mechanism of the contour during indentation on surface grains with different orientations is also discussed in the study.